2019
DOI: 10.1177/0734242x19843988
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soil types and ammonia concentrations on the contribution of ammonia-oxidizing bacteria to CH4oxidation

Abstract: Irrigation of stabilized landfill leachate to landfill cover soil is a cost-effective operation for leachate treatment. The contribution of ammonia-oxidizing bacteria (AOB) in the cover soil to CH 4 oxidation, however, is unclear, because AOB and methane-oxidizing bacteria (MOB) can co-oxidize CH 4 and NH 4 + -N. Thus, the contribution of AOB and the inhibitory effect of NH 4 + -N to CH 4 oxidation were determined by using an acetylene pretreatment discrimination method. The results showed that the contributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The previous authors found that soil OM mineralization in soils results in CO 2 evolution; hence, vegetation that recycles higher OM is most likely to produce higher CO 2 . Also, soil NH 4 + ‐N is known to inhibit soil methane oxidation into CO 2 (Bian et al., 2019; Y. Wang et al., 2014); thus, the higher soil CO 2 was expected in the woodland riparian buffer since the vegetated riparian buffers were not directly fertilized. The values observed in the current study are in line with other authors, particularly Tufekcioglu et al.…”
Section: Discussionmentioning
confidence: 99%
“…The previous authors found that soil OM mineralization in soils results in CO 2 evolution; hence, vegetation that recycles higher OM is most likely to produce higher CO 2 . Also, soil NH 4 + ‐N is known to inhibit soil methane oxidation into CO 2 (Bian et al., 2019; Y. Wang et al., 2014); thus, the higher soil CO 2 was expected in the woodland riparian buffer since the vegetated riparian buffers were not directly fertilized. The values observed in the current study are in line with other authors, particularly Tufekcioglu et al.…”
Section: Discussionmentioning
confidence: 99%
“…In the current experiment, likely, the inhibitory role of NH 4 + ‐N on CH 4 oxidation to CO 2 in the N‐fertilized no buffer control and upslope pasture resulted in the exponential increase cumulative soil CH 4 fluxes associated with increases in soil mineral N (Figure 7) as well as a significant correlation between CH 4 and mineral N (Figure 6). The inhibitory effect of NH 4 + ‐N fertilizer addition on CH 4 oxidation could be attributed to the fact that CH 4 monooxygenase of methanotrophs can oxidize a variety of substrates besides soil CH 4 (Bian et al., 2019; Wang et al., 2014). Thus, the majority of higher soil CH 4 fluxes by the upslope pasture and no‐buffer control than in the vegetated downslope riparian buffer strips during the experimental period (Figure 4B) could have resulted from the N fertilizer directly applied into the former treatments.…”
Section: Discussionmentioning
confidence: 99%
“…For the biodegradation of polymers, it was found that certain bacterial strains were able to biodegrade plastics in soil [19,[24][25][26][27][28], in contrast to other studies that used bacterial consortia [29][30][31][32], resulting in a significant reduction in these contaminants as well as a reduction in biodegradation time by 90 days [30] and 30 days [31], demonstrating that the symbiotic capacity of bacteria can be a viable option. Finally, there is the bioremediation of organic matter, the most commonly used techniques were the isolation of bacteria [33,34], and some studies specifically investigated the bioremediation capacity of Pseudomonas [35][36][37] and bacterial mixtures [38][39][40][41].…”
Section: Bioremediation Techniquesmentioning
confidence: 99%
“…Most of these studies focus on evaluating the efficiency of bioremediation by bacterial consortia [38][39][40][41]. Some of these studies used pseudomonas [35][36][37] and other studies selected specific bacteria [33,34], which generally resulted in a high degradation capacity of these contaminants.…”
Section: Organic Mattermentioning
confidence: 99%